Miniaturized frequency-reconfigurable single-feed multi-band antenna with bandwidth enhancement for wireless applications - Boukarkar, Abdelheq; Rachdi, Satouh; Merabet, Mohamed Amine; Baguigui, Sami; Adda Benziane, Khalil (Journal of electromagnetic waves and applications, 2024)
We propose a miniaturized frequency-reconfigurable multiband antenna with bandwidth enhancement. The main radiating patch is shorted from one edge to reduce the antenna footprint. An inverted U-shape microstrip line is integrated onto the antenna structure to excite more resonant frequencies. Indeed, by shorting the U-shape's arms, seven frequency bands can be created and controlled. The activation of the two p-i-n diodes is ensured by employing a simple symmetrical DC bias network. Furthermore, by adjusting the arms' lengths, two resonances are combined to enhance the working bandwidth. Measurements reveal that the antenna resonates around the operating frequencies of 2.91 GHz, 3.55 GHz, 3.69 GHz, 3.83 GHz, 4.14 GHz, 4.18, and 4.24 GHz. The antenna exhibits stable patterns, with a measured peak gain and efficiency of 5.5 dBi and 86%, respectively. The antenna is compact; thus, it is recommended in wireless systems requiring multiband function with stable patterns and a reduced area.